KEDUDUKAN HUKUM DAN TANGGUNG JAWAB PENDIRI YAYASAN MENURUT UNDANG UNDANG NOMOR 28 TAHUN 2004 PADA YAYASAN SALAFIYAH ASYAFIâIYAH DI TUBAN - , NURIL AINI; , Prof. Dr. Abdul Ghofur Anshori, S.H., M.H ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aiming to know and understand about law position and responsibility of foundation establisher at Salafiyah Asyafiâiyah before and after the according of foundation members, and hindrance factors in according of basic constitution of foundation and what efforts that already done to fix it problems. Research format is normative juridical research and empiric juridical. It is means this research focused by researches which supported by other field research. Beside it focuses at the behaviors which happened in society. Responders of this research are Salafiyah Asyafiâiyah Foundation and supported by some sources. Hypotheses of research is shows about law position and responsibility of foundation establisher at Salafiyah Asyafiâiyah before and after the according of basic constitution of foundation number 28/ 2004: 1. Before basic constitution of foundation has been legal, the foundation is executed by a leader, vice leader, treasurer, and secretary. This is noticed in Chapter 5 Salafiyah Asyafiâiyah Foundation made by Sugianto, SH. Notaries from Tuban. 2. After has been legal, basic constitution of foundation is executed by controller and supervisor. This rule due to Chapter 6 Salafiyah Asyafiâiyah Based Constitution of Foundation The hindrance factors from Salafiyah Asyafiâiyah Foundation members due to basic constitution of foundation number 28/ 2004 is about less of human resources, no contra prestige for the foundation members, no Government Regulation, and lack of socialization from the government.